Inflation Uncertainty at Short and Long Horizons: Turkey - Tuna, Gulcay; Payaslioglu, Cem (Bilgesel Yayincilik San & Tic Ltd, 2011)
This paper investigates the link between inflation in Turkey and its uncertainty in understanding the costs of inflation and its implications for the policy makers. The study is based on the arguments of Ball and Cecchetti (1990) which distinguish between short-term and long-term uncertainty and Kim's (1993) unobserved component with Markov-switching heteroscedasticity. The empirical results for the period of January 1995-January 2008 suggest that inflation uncertainty is due to transitory shocks rather than the permanent shocks. The link between inflation and inflation uncertainty due to permanent shocks indicates weak negative association between the level of inflation and long-run inflation uncertainty except the crises periods. This result is not consistent with the hypothesis of Ball and Cecchetti (1990). The implication of the empirical results support the idea of unsuccessful monetary policies during high inflation period till 2001 that were characterized by frequent policy shifts and mismanagement of the economy while a strong commitment of the monetary authorities to the inflation targeting strategy reversed the stance of the monetary policy after the 2001 crises.
Keywords: Inflation Uncertainty; Markov Switching Model